Treatment of tuberculosis - Zellweger, Jean-Pierre (Henry Stewart Talks, 2021)
History of chemotherapy, Current first-line drugs and mechanisms of action, Main second-line drugs, Standard regimens, Special situations: pregnancy, children, drug interaction, Person-centered approach, DOT, Other options for tuberculosis treatment